Pengelolaan Limbah Organik Rumah Tangga Melalui Edukasi Komposter dan Eco Enzyme di Kelurahan Rungkut Menanggal Surabaya - Dilan Serviako Sinaga; Salsabilla Septyant Putri; Yessy Arye Yustraini; Shalsabila Titanie Harianto; Audya Dwi Tira Widodo; Tukiman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
The community service deducation about composter and eco enzyme education was held at RT 03 RW 01, Rungkut Menanggal, Surabaya, to respond the problem of household organic waste management that still not effective. This activity aims to give the residents knowledge and skills for change organic waste into eco-friendly product by training them how to make composter and eco enzyme. The method used including problem identification through observation, coordination with local community leaders, making educational materials, deliver it by demonstration, and evaluation. The result show positive response and active participation from the residents in understanding and doing sustainable waste management practices. The residents start to understand that organic waste like fruit peels and food leftovers can be turn into natural cleaner or fertilizer for plants. This activity becomes the first step to build ecological awareness and social responsibility for the environment around them.